Analisis Efektivitas Program Kartu Jakarta Pintar Plus (KJP Plus) Tingkat Sekolah Menengah Pertama (SMP) di Jakarta Selatan - Siti Sarah Nurfadlia; Izzatusholekha Izzatusholekha (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to determine the effectiveness of the Jakarta Smart Card Plus (KJP Plus) Program at the Junior High School (SMP) level in South Jakarta in 2024. The program is an initiative by the Provincial Government of DKI Jakarta to ensure access to education for underprivileged families. This research employs Sutrisno’s (2007) program effectiveness theory, which includes five key indicators: program understanding, target accuracy, timeliness, goal achievement, and real change. The research method used is a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation involving informants from the South Jakarta Region I Education Sub-Department, school principals, students, and parents of KJP Plus beneficiaries. The results of the study indicate: (1) Understanding of the program is still uneven, particularly among parents who lack knowledge about the mechanism and use of KJP Plus; (2) Target accuracy is not optimal, as some recipients are economically capable, such as those who own cars or fall into higher welfare deciles; (3) The timeliness of fund distribution is generally good, although there are still some administrative delays; (4) Goal achievement is evident through reduced school dropout rates and increased educational participation, but not evenly across all areas; and (5) Real change is felt by most beneficiaries through easier access to education and provision of school supplies, although misuse of funds for non-educational purposes is still present. Overall, the effectiveness of the KJP Plus program at the SMP level in South Jakarta is deemed suboptimal, highlighting the need for improved data accuracy, stricter fund usage monitoring, and broader program socialization.